The Influence of Macroeconomic Variables on Non-Performing Loan (NPL) at PT Bank Mandiri (Persero) Tbk - Radhianas, Binky Mohammad; Matoati, Rindang; Viana, Eka Dasra; Dewi, Farida Ratna; Kaewlaead, Chuta (GREENOMIKA, 2024)
In recent years, Bank Mandiri's non-performing loan (NPL) ratio has been on a relatively stable decline until the COVID-19 pandemic in 2020 quarter I put pressure on the Indonesian economy. Since then, Bank Mandiri's NPL ratio has increased significantly due to the global economic recession that also occurred in Indonesia in 2020 quarter III. This study aims to analyse the effect of macroeconomic variables such as gross domestic product, inflation, interest rates, and exchange rates on non-performing loans (NPL) specifically at Bank Mandiri. This study uses secondary data in the form of historical data of related variables and Vector Error Correction Model (VECM) to estimate the dynamics of long-term and short-term relationships between variables. The results of this study indicate that macroeconomic variables such as BIRATE, INF, and LNPDB significantly affect Bank Mandiri's NPLs in the long-run dynamics, while LNKURS is statistically significant in the short-run dynamics. Keywords: Macroeconomic, Non-Peforming Loan, VECM